2000
DOI: 10.1136/oem.57.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Associations of self estimated workloads with musculoskeletal symptoms among hospital nurses

Abstract: Objectives-To investigate the prevalence of neck, shoulder, and arm pain (NSAP) as well as low back pain (LBP) among hospital nurses, and to examine the association of work tasks and self estimated risk factors with NSAP and LBP. Methods-A cross sectional study was carried out in a national university hospital in Japan. Full time registered nurses in the wards (n=314) were selected for analysis. The questionnaire was composed of items on demographic conditions, severity of workloads in actual tasks, self estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
158
10
18

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 43 publications
16
158
10
18
Order By: Relevance
“…Nurses in these settings, therefore, may experience heavier work demands due to higher patient acuity and greater work complexity, thus increasing the risk of injury (Ando et al, 2000;Menzel, Brooks, Bernard, & Nelson, 2004;Trinkoff, Lipscomb, Geiger-Brown, Storr, & Brady, 2003). While it is reasonable to assume that, like teaching hospitals, the risk of injury is higher for nurses in hospitals that offer more high technology services, no studies have described the effect of technological complexity on work-related injuries among nurses.…”
Section: Hospital Environment-characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses in these settings, therefore, may experience heavier work demands due to higher patient acuity and greater work complexity, thus increasing the risk of injury (Ando et al, 2000;Menzel, Brooks, Bernard, & Nelson, 2004;Trinkoff, Lipscomb, Geiger-Brown, Storr, & Brady, 2003). While it is reasonable to assume that, like teaching hospitals, the risk of injury is higher for nurses in hospitals that offer more high technology services, no studies have described the effect of technological complexity on work-related injuries among nurses.…”
Section: Hospital Environment-characteristicsmentioning
confidence: 99%
“…Higher patient acuity and greater work complexity have been linked to increased work-related injuries among nurses (Ando et al, 2000;Geiger-Brown et al, 2004;Lundstrom et al, 2002). Nurses are more likely to encounter time-sensitive situations that require immediate action when patient acuity is high.…”
Section: 23mentioning
confidence: 99%
“…Esse problema acomete trabalhadores em países Rev Bras Enferm, Brasília 2007 nov-dez; 60(6): 701-5. desenvolvidos e também em subdesenvolvidos, levando-os a diferentes graus de incapacidade funcional. Em todo o mundo, esse distúrbio gera aumento de absenteísmo e de afastamentos temporários ou permanentes do trabalhador e também produz custos expressivos em tratamento e indenizações (1,(3)(4)(5)(6)(7)(8) .…”
Section: Introductionunclassified
“…Pesquisas realizadas em vários países, exibem prevalências superiores a 80% de ocorrência de distúrbios musculoesqueléticos em trabalhadores de enfermagem (5,6,8,12,13) . Estudos brasileiros mostram prevalências entre 43 a 93% desses distúrbios (10,14,15) .…”
Section: Introductionunclassified
“…Similarly, Kim and colleagues found a modest increase in risk (OR=1.14; CI=1.08-1.19) for physical demands among PAS providers (Kim et al, 2010). Other studies of care providers have also found challenges in identifying the role of physical risk factors in WRMSDs or related disability (Ando et al, 2000;Simon et al, 2008), or determining the most problematic physical risk factor in home care (Cheung et al, 2006;Ono et al, 1995). Most of these studies, like ours, were self report surveys, and lacked validation from medical or disability records, which may lead to misclassification of cases or imprecision of the models.…”
Section: Temporal Factorsmentioning
confidence: 95%